2021
DOI: 10.1186/s13002-021-00456-x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal ethnoecology: observed habitat preferences and the perception of changes in fungal abundance by mushroom collectors in Poland

Abstract: Background Scientists frequently raise the topic of data deficiency related to the abundance and distribution of macrofungi in the context of climate change. Our study is the first detailed documentation on locals’ perception of fungal ecology which covers a large mycophilous region of Europe (Mazovia, Poland). Methods A total of 695 semi-structured interviews were carried out among local informants in 38 localities proportionally distributed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…In the first place, there is a great variety of studied factors (various macro and microclimatic factors, edaphic factors); hence, it is difficult to perform a comparison with the literature data. The majority of studies address the effects of a single or just a few factors such as drought, precipitation, air temperature, CO 2 level, or soil pH [ 33 , 34 , 35 , 36 , 37 ], while some studies deal with only one specific group of factors, most commonly edaphic [ 38 , 39 , 40 ], climatic [ 32 , 41 ] or habitat factors [ 42 , 43 , 44 ]. In addition, there is a difference in terms of analyzed data as well as examined mycocenoses.…”
Section: Introductionmentioning
confidence: 99%
“…In the first place, there is a great variety of studied factors (various macro and microclimatic factors, edaphic factors); hence, it is difficult to perform a comparison with the literature data. The majority of studies address the effects of a single or just a few factors such as drought, precipitation, air temperature, CO 2 level, or soil pH [ 33 , 34 , 35 , 36 , 37 ], while some studies deal with only one specific group of factors, most commonly edaphic [ 38 , 39 , 40 ], climatic [ 32 , 41 ] or habitat factors [ 42 , 43 , 44 ]. In addition, there is a difference in terms of analyzed data as well as examined mycocenoses.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe where there is a longer history of monitoring macrofungi (which form aboveground fruiting bodies, a category which includes many EMF), reports paint a similar picture, suggesting that many macrofungi are declining (Senn-Irlet et al 2007). All 22 native species of hydnoid fungi (forming fruiting bodies with tooth-like projections) in The Netherlands and Northwestern Europe show declines in fruiting bodies since 1950 (Arnolds 2010), and fungal ethnoecology studies revealed that 53% of mushroom collectors in Poland report a steady decrease in macrofungi (Kotowski et al 2021). The decline of mycorrhizal fungi generally is more difficult to assess because this category includes fungi that do not form large fruiting bodies aboveground, such as AMF.…”
Section: Reasons For Concernmentioning
confidence: 99%
“…The information collected on mushroom picking preferences shows that local knowledge generally does not differ from scientific knowledge [16]. Analysing public perceptions of mushrooms can help to improve knowledge about local changes in mushroom diversity and provide new assessments related to analysing the large-scale occurrence of macrofungi and their harvesting.…”
Section: Introductionmentioning
confidence: 99%